Riverine macroplastic survey along the segments of Tullahan River in Metro Manila, Philippines - Talavera, Allyza L.; Dalida, Lorrayne Faye M.; Diola, Ma. Brida Lea D. (Frontiers in Environmental Science, 2024)
The Philippines is one of the world's main contributors to global marine plastic pollution. However, field data remains scarce, so model estimates of riverine plastic pollution may be inaccurate. This paper aims to characterize the macrolitter observed along the Tullahan River, with focus on plastics, passing through the barangays of Quezon City and Valenzuela City in Metro Manila. The impact of solid waste management and land use activities on plastic flux were also investigated. For the floating litter, visual counting and float method were used to determine the plastic flux and river velocity, respectively. Riverbank litter was collected manually to characterize it based on plastic product and polymer type. Results show that the macroplastic flux was lowest on the site where residential houses are farthest from the stream. Waste characterization revealed that riverbank litter was primarily plastic – 30%-41% were residuals, and 5%-21% were recyclables. Both methods revealed that wrappers and thin PE plastics are the top contributors to riverine macroplastic pollution. Therefore, the entry of macroplastics into the river may be due to land use activities and weak enforcement of existing solid waste management (SWM) policies. The points discussed in the study can help in improving SWM and land use planning. The results can also increase the accuracy of model estimates.